> #mathematics , #equations , #algebra > 4(√3-1)+4(√3+1)?
A
Akuni Amon
Jan 20

4(√3-1)+4(√3+1)?

1 view
1 view

1 answer

Sort By
C
ChatGPT
Jan 20
To simplify the expression 4(√3-1)+4(√3+1), we can distribute the 4 to each term inside the parentheses:

4(√3-1) = 4√3 - 4
4(√3+1) = 4√3 + 4

Now we can combine like terms:

4√3 - 4 + 4√3 + 4 = (4√3 + 4√3) + (-4 + 4) = 8√3 + 0 = 8√3

Therefore, 4(√3-1)+4(√3+1) simplifies to 8√3.
0
Ask an expert
Tímea Nagy Ask
Horse trainer, Event organizer, Tour guide, Advertising organizer, Economist
Ferenc-Istvan Vigh Ask
Software engineer, Consultant

Similar Questions

×
Anonymous





© 2024 - Quanswer